ENTREPRENEURIAL CULTURE OF KUBE - Yuce Sariningsih (SAMPURASUN, 2017)
This study investigated Kelompok Usaha Bersama (KUBE) which was managed by women or Poor Women Business Group Program was a social service program in economic field which was under supervised by Ministry of Social Affairs of the Republic of Indonesia to eradicate poverty, where entrepreneurship as an important successful key indicator of their business. Entrepreneurship also occurred in social service agencies and has long described with terms such as new, innovative, flexible, dynamic, creative, and risk taking. However, entrepreneurship did not yet a business spirit by most KUBE in West Java Indonesia. One of great opportunity in KUBE business which was needed an entrepreneurial spirit was waste bank. Decentralized waste banks, trash banks, garbage banks or Bank Sampah as they are called in Indonesia are a new convincing concept for waste management. This study used a survey to investigate the perception of women's business group at West Java who joined in Kelompok Usaha Bersama (KUBE) on waste bank. The respondent of this study were 111 (one hundred and eleven) poor women who received business aid in form of money and goods for the development of their business activities. The waste bank was still not popular among KUBE’s member, they are set up in neighborhoods typically for about 1000 residents and are usually run by poorer people who wish to increase their income. Bank customers bring all non-organic waste to the banks where it was treated like a deposit. Transactions were recorded preferably in a bank book that the customer hold or alternatively in lists kept by the bank. Ministry of Environment of Indonesia promoted Waste Banks as the new strategic program. According to the Ministry, Garbage Management with a lot of positive impacts through the waste bank development program was inseparable from the participation of people, especially from the grassroots level.